Review on antibacterial flavonoids from genus Erythrina: Structure-activity relationship and mode of action - Tati Herlina; Abd Wahid Rizaldi Akili; Vicki Nishinarizki; Ari Hardianto; Jalifah Binti Latip (Heliyon)
The Fabaceae family, particularly genus Erythrina, is renowned for significant medicinal properties. These plants have been used as natural remedies to address various health issues and are rich in flavonoids. Therefore, this review aimed to provide a comprehensive overview of antibacterial activity, structure-activity relationship, especially against drug-resistance Staphylococcus aureus, and mode of action for flavonoids isolated from Erythrina. Data were collected from reputable electronic scholarly resources focusing on publications from 2000 to 2022. The results showed that the evaluated flavonoids include 31 % pterocarpans, 22 % flavanones, 20 % isoflavanones, 18 % isoflavones, 4 % isoflavans, 3 % isoflav-3-enes, 1 % 3-arylcoumarins, and 1 % coumestans. Most of these compounds in Erythrina plants were extracted from the roots and stem bark. Among these group of flavonoids, pterocarpan stands out as the most active class against S. aureus. Structure-activity relationship study emphasized pivotal contribution of the prenyl functional group to enhance antibacterial activity of flavonoids. Increasing the number of prenyl groups enhanced antibacterial effectiveness while modifying the group reduced this activity. The proposed antibacterial mechanisms of these flavonoids include the suppression of nucleic acid synthesis, disruption of cytoplasmic membrane function, and modulation of energy metabolism. Among the potent antibacterial flavonoids from genus Erythrina, compound 3,9-dihyroxy-10-γ,γ-dimethylallyl-6a,11a-dehydropterocarpan was found as the most potent against Methicillin-Resistant Staphylococcus aureus (MRSA) through the inhibition of nucleic acid synthesis. Other common flavonoids such as genistein, daidzein, apigenin, and luteolin exert antibacterial activity through the inhibition of ATP synthase.